Strong effect of magnetic field on the edge luminescence line width in diluted magnetic narrow-gap Hg₁₋xMnxTe - Mazur, Yu.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1998)
Peculiarities of photoluminescence in narrow-gap Hg₁₋xMnxTe (0.09 < x < 0.11) under variation of both magnetic field and temperature are studied. A strong resonance enhancement of the edge emission and a narrowing of the line width to less than 2.5 meV were detected. The photoluminescence behaviour observed can be well described by the model of a magnetically trapped exciton. Досліджено особливості фотолюмінесценції у вузькозонних твердих розчинах Hg₁₋XMnXTe (0,09 < x < 0,11) у випадку комбінованого впливу магнітного поля та температури. Виявлено сильне резонансне підсилення крайової люмінесценції та звуження ширини її лінії до значень < 2,5 meV. Спостережувана поведінка фотолюмінесценції інтерпретується ,в рамках моделі магніто-захопленого екситона. Исследованы особенности фотолюминесценции в узкозонных твердых растворах Hg₁₋XMnXTe (0,09 < x < 0,11) при комбинированном воздействии магнитного поля и температуры. Обнаружено сильное резонансное усиление краевой люминесценции и сужение ширины ее линии до значений < 2,5 meV. Наблюдаемое поведение фотолюминесценции интерпретируется в рамках модели магнито-захваченного экситона.